David Gentilcore: Italy and the Potato: A History, 1551–2000 & David Gentilcore: Pomodoro! A History of the Tomato in Italy - Jaine, Tom (Petits Propos Culinaires, 2012)
David Gentilcore: Italy and the Potato: A History, 1551–2000: Continuum, 2012, 257pp., hardback, £60.00.David Gentilcore: Pomodoro! A History of the Tomato in Italy: Columbia University Press, 2010, 254 pp., hardback, £18.95.